Phytochemical composition, antioxidant, antihyperlipidemic, and hepatoprotective effects of phenolic components of Iraqi sumac (Rhus coriaria) - Hassan, Sarah Falah; Abu Raghif, Ahmed R.; Kadhim, Enas Jawad; Ridha-Salman, Hayder; Abbas, Alaa Hamza (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Hyperlipidemia is a pathogenic disease associated with significant cardiovascular complications. Rhus coriaria, traditionally recognized as sumac, is abundant in numerous phenolic constituents that enhance its antioxidant, antibacterial, and anti-inflammatory characteristics. The aim was to investigate the phytochemical and pharmacological attributes of phenolic constituents of R. coriaria. Material and methods. 32 male albino mice were assigned at random into 4 groups (n=8). Group 1 (control), group 2 (induced), group 3 (atorvastatin) and group 4 (phenolic). All groups received a diet that was rich in fat for a duration of 28 days, except the control group, which instead consumed a standard diet. Group 2 received no treatment, while group 3 and group 4 received atorvastatin 10 mg/kg and phenolic fractions of R. coriaria 500 mg/kg, respectively, for a further 28 days. Lipid profiles, oxidative indicators, biochemical parameters, and liver histopathological examination were estimated. Results. Phenolic fractions substantially improved total cholesterol (167.5±2.4 vs. 280.4±17.6 mg/dL), triglycerides (181.1±12.5 vs. 238.6±11.05 mg/dL), low-density lipoprotein (109.0±1.6 vs. 209.2±16.8 mg/dL), and very low-density lipoprotein (36.2±2.5 vs. 47.7±2.21), while raising high-density lipoprotein levels (42.3±1.8 vs. 23.5±2.3 mg/dL) as opposed to the induced group (p<0.05). Furthermore, the phenolic constituents significantly reduced liver enzyme activities like alanine transaminase (27.4±1.8 vs. 45.2±2.8 U/L), aspartate aminotransferase (31.7±2.1 vs. 44.9±2.0 U/L), and alkaline phosphatase (28.0±2.1 vs.50.9±1.9 U/L), and decreased total blood bilirubin (0.6±0.08 vs. 1.7±0.1 mg/dL) and albumin (4.7±0.7 vs. 6.6±0.3 g/dL) when compared to the induced nontreated group (p<0.05). Phenolic treatment also alleviated tissue malondialdehyde (221.09±3.2 vs. 475.98±44.02 nmol/mL) and increased reduced glutathione (35.48±1.86 vs. 11.65±0.78 μg/mL) as compared to the group without induced non-treated group (p<0.05) and restored liver histopathological changes. Conclusion. Phenolic compounds have the potential to treat hyperlipidemia due to their anti-oxidative and anti-inflammatory properties.